The Ability of Family Caregivers to Prevent Relapse of Schizophrenia - Iswanti, Dwi Indah; Lestari, Sri Puji; Mendrofa, Fery Agusman Motuho (Jurnal Keperawatan Jiwa, 2024)
Schizophrenia relapse occurs due to the family's inability to care for and modify the environment at home. This occurs due to low knowledge of family care, not being taken to mental health services, refusal of treatment from patients, and high emotional expression in the family environment. This study aimed to analyze the ability of family caregivers to prevent relapse of schizophrenia. Quantitative research design with a cross-sectional approach. The sample was 70 families who are caregivers of schizophrenia at the health center in Semarang City with a purposive sampling technique. Instruments in the form of a questionnaire developed from several concepts and tested validity reliability again.  Data analysis using Spearman rank correlation with 95% significance. The results showed that there was a strong and unidirectional relationship between the family's ability to care for schizophrenia and relapse prevention (p=0.000, r=0.628). The better the family's ability to care, the better the relapse prevention efforts made. Mental nurses can provide repeated education and training to improve family knowledge of caring for schizophrenia at home.